Social-Emotional Management to Promote Quality in Education: A Training Program for Teachers - María del Carmen Díez González; Rafael Marcos-Sánchez; Alicia Zaragoza-Benzal; Daniel Ferrández (MDPI AG, 2024)
Social-emotional management in educational centers is a key element nowadays to achieve quality education, having become even more important after the pandemic period caused by the COVID-19 virus. Training programs in socioemotional skills, such as the EmocionaTFamilia program, are necessary to enhance teachers' soft skills. This research aims to understand how the EmocionaTFamilia program promotes socioemotional skills to deal with teaching management and practice, as well as the fear generated by the pandemic. For this purpose, quantitative and qualitative evaluative research on the program has been carried out using the TMMS and COVID-19 fear online questionnaires, in which emotional attention, clarity, and repair, as well as fear, have been analyzed. A total of 21 participants, including the school's management team and elementary and secondary teachers, participated in an educational institution located in Madrid, Colombia. The age of the sample ranged from 22 to 54 years old, with 1 to 20 years of teaching experience. The program was implemented in six sessions over three months, sequenced at three levels: the development of awareness and basic training in emotional education; the development of emotional competences; and coping with fear. The results show that, once the program has been implemented, there is an improvement in the means of all the emotional dimensions and in coping with fear in the study population. These dimensions allow for becoming aware of emotions and learning to place them in the right place, acquiring awareness to accompany students in their strengths and weaknesses. Encouraging listening to peers to transform fears into gratitude is promoted. Thus, the findings of this research reveal a scenario that underscores the need for adequate continuous training in socioemotional skills to enable the management of emotions and fear in the classroom.